69.1k views
2 votes
Dahlia is simplifying (3t)^4 using these steps:

(3t)^4 =3t•3t•3t•3t =3•3•3•3•t•t•t•t

Although Dahlia is correct so fast which step could she have used instead to simplify the expression (3t)^4 ?


A. 3t =3t⁴
B. 3⁴ =81t
C. 4(3t)= 12t
D. 3⁴t⁴ =81t⁴

User Watsonic
by
4.8k points

2 Answers

1 vote

D. 3⁴t⁴ =81t⁴.

81t⁴ is going to be your answer.

Here is how you get it:

3t(3)t(3)t(3)t =3*t*3*t*3*t*3*t

=81*t^4

=81t^4

User Dudu
by
4.4k points
0 votes
to simplify, we'd simply distribute the power of 4 to each individual within the parentheses

answer = D.
User CrveniZg
by
5.9k points